Answer:
392
Step-by-step explanation:
Hello from MrBillDoesMath!
Answer:
(1/3) x = (5/6)
Discussion:
I think you are asking for this equation:
(1/3) x = (5/6) => multiply both sides by 3
(1/3) 3 x = (5/6) 3 => as (1/3) *3 = 1
x = 5*3/6
x= 15/6
x = 5/2 = 2.5
Thank you,
MrB
Answer:
option A
Step-by-step explanation:
option A is the correct answer of this question.
<em><u>plz </u></em><em><u>mark</u></em><em><u> my</u></em><em><u> answer</u></em><em><u> as</u></em><em><u> brainlist</u></em><em><u> plzzzz</u></em><em><u>.</u></em>
<em><u>hope</u></em><em><u> this</u></em><em><u> will</u></em><em><u> be</u></em><em><u> helpful</u></em><em><u> to</u></em><em><u> you</u></em><em><u> </u></em>
Answer:
- -32x² +8x -8
- See below about the process
Step-by-step explanation:
The simplified expression is ...
3x(x -12x) +3x² -2(x -2)²
= 3x(-11x) +3x² -2(x² -4x +4) . . . . . simplify contents of parentheses
= -33x² +3x² -2x² +8x -8 . . . . . . . .eliminate parentheses
= (-33 +3 -2)x² +8x -8 . . . . . . . . . . group the coefficients of like terms
= -32x² +8x -8
Answer:
x value: start with 0 and go up by 1
y value:start with 10 and each week is 5 more than previous week
Step-by-step explanation: